2017
DOI: 10.1007/s12032-017-1052-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary metastatic osteosarcoma: results of a prospective study in children given chemotherapy and interleukin-2

Abstract: To improve the poor prognosis for children with metastatic osteosarcoma (OS), interleukin-2 (IL-2) was added to the standard treatment due to its capacity to activate lymphocytes and differentiate lymphocyte subsets into lymphokine-activated killer (LAK) cells that are capable of recognizing and killing various tumor cells. This study concerns a cohort of unselected patients aged < 18 years with metastatic OS, who were treated with IL-2, high-dose methotrexate, doxorubicin, cisplatin, ifosfamide, LAK reinfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…In one study, Meazza and colleagues reported the outcomes of 35 pediatric OS patients with macroscopic OS treated with surgery and combinatorial chemoimmunotherapy comprised of IL-2, MAP, ifosfamide, and lymphokine-activated killer (LAK) cell infusion. While the study was not designed to determine the immunobiologic benefit derived from IL-2 and LAK cell infusion, adverse effects associated with IL-2 therapy were tolerable (grade I and II) with most common side effects being fever, flu-like symptoms, hypotension, and cytokine release syndrome (248). In a different study, Schwinger and colleagues reported the tolerability and activity of single-agent, high-dose IV IL-2 therapy in 10 pediatric patients, in which 4 adolescents had metastatic OS (249).…”
Section: Immune Modulatorsmentioning
confidence: 99%
“…In one study, Meazza and colleagues reported the outcomes of 35 pediatric OS patients with macroscopic OS treated with surgery and combinatorial chemoimmunotherapy comprised of IL-2, MAP, ifosfamide, and lymphokine-activated killer (LAK) cell infusion. While the study was not designed to determine the immunobiologic benefit derived from IL-2 and LAK cell infusion, adverse effects associated with IL-2 therapy were tolerable (grade I and II) with most common side effects being fever, flu-like symptoms, hypotension, and cytokine release syndrome (248). In a different study, Schwinger and colleagues reported the tolerability and activity of single-agent, high-dose IV IL-2 therapy in 10 pediatric patients, in which 4 adolescents had metastatic OS (249).…”
Section: Immune Modulatorsmentioning
confidence: 99%
“…Although responses to IL-2 have been reported in clinical trials in patients with various malignancies, only clinical trials for renal cell carcinoma and melanoma observed efficacy of IL-2 [34]. Only a few clinical trials of IL-2 for sarcomas have been reported [35, 36]. In a clinical trial using IL-2 with or without reinfusion of LAK for patients with metastatic osteosarcoma, 3-year event-free and overall survival rates were 34% and 45%, respectively [35].…”
Section: Role Of the Immune System And Advancement In Immunotherapmentioning
confidence: 99%
“…Only a few clinical trials of IL-2 for sarcomas have been reported [35, 36]. In a clinical trial using IL-2 with or without reinfusion of LAK for patients with metastatic osteosarcoma, 3-year event-free and overall survival rates were 34% and 45%, respectively [35]. Immunotherapy using a monoclonal antibody against the tumor-associated disialoganglioside GD2, granulocyte macrophage colony-stimulating factor (GM-CSF), and IL-2 was associated with a significantly improved outcome as compared with standard treatment in patients with neuroblastoma [36].…”
Section: Role Of the Immune System And Advancement In Immunotherapmentioning
confidence: 99%
“…Osteosarcoma is the most common primary malignant bone tumour in children and adolescents [1]. It is characterized by rapid progression, early pulmonary metastasis, poor prognosis and recurrence [2][3][4]. While the 5-year survival rate of patients with osteosarcoma is approximately 65%, that of patients with metastatic osteosarcoma is only 25% [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether surgery is beneficial for stage IV osteosarcoma patients with extensive metastases remains unclear. There have been studies that have favoured non-resection therapies, such as chemotherapy or radiotherapy, for patients with multiple unresectable metastases [2,12]. Surgical resection is not always feasible due to challenges such as large tumours, various sites of origin, poor physical condition, and various complications after resection.…”
Section: Introductionmentioning
confidence: 99%